Comissões próprias de avaliação de universidades do sudeste brasileiro: o que dizem os documentos e o que ocorre na prática - Júlia Flávia Araújo Carvalhaes (2018)
An integral part of the National System for the Evaluation of Higher Education (Sinaes), the internal evaluation carried out by the Self Assessment Committee (CPA) within the Higher Education Institutions (HEIs) is an opportunity for institutions to know their potentialities and weaknesses of the opinion of the academic community. Compulsory composition in HEIs, the CPA is responsible for coordinating the process of institutional self-assessment guided by national guidelines prepared by the National Commission for the Evaluation of Higher Education (Conaes) in the years 2004 and 2014. Although guidelines are drawn up, these guidelines do not contemplate the objectives, methodology and routine of work to be used by the CPAs, which are at the discretion of each institution, which is why it is assumed that despite the national guidelines, commissions evaluation of different HEIs lead to internal evaluation in a varied way depending on the institutional characteristics and contexts in which they are inserted. In this sense, this research aimed to investigate the work dynamics of CPAs of public and private universities in the Southeast through comparative analysis. This was operationalized through the application of questionnaires, interviews and documentary analysis. Sixty-two questionnaires were applied to coordinators of evaluation committees of universities in Southeastern Brazil, of which 23 (twenty-three) were answered. From the analysis of the answers obtained, characteristics of the respondent universities and availability of the researcher's displacement, nine universities were selected for interviews with CPA members. From these, it was possible to operationalize the interview in five universities, three in the state of Rio de Janeiro and two in the state of Minas Gerais. The data obtained showed that although they present a common scope of assignments and perform functions closely related to the guidelines document produced by Conaes, the CPAs present variations regarding the evaluation scope, the forms of operationalization of the institutional evaluation, how perceive their role in the institution and in the conceptions they present about what self-evaluation is. Besides the variation of work dynamics among institutions, there are indications that there is inter-institutional variation depending on the composition of the evaluation committee itself and the historical moment experienced by the universities